The use of whole-body computed tomography in major trauma: variations in practice in UK trauma hospitals. Issue 10 (27th January 2017) - Sammy, Ian Ayenga; Chatha, Hridesh; Bouamra, Omar; Fragoso-Iñiguez, Marisol; Lecky, Fiona; Edwards, Antoinette
Abstract : Introduction: Whole-body CT (WBCT) use in patients with trauma in England and Wales is not well documented. WBCT in trauma can reduce time to definitive care, thereby increasing survival. However, its use varies significantly worldwide. Methods: We performed a retrospective observational study of Trauma Audit and Research Network (TARN) data from 2012 to 2014. The proportion of adult patients receiving WBCT during initial resuscitation at major trauma centres (MTCs) and trauma units/non-designated hospitals (TUs/NDHs) was compared. A model was developed that included factors associated with WBCT use, and centre effects within the model were explored to determine variation in usage beyond that expected from the model. Results: Of the 115 664 study participants, 16.5% had WBCT. WBCT was performed five times more frequently in MTCs than in TUs/NDHs (31% vs 6.6%). In the multivariate model, increased injury severity, low GCS, shock, comorbidities and triage category increased the chances of having a WBCT, but there was no consistent relation with age. High falls and motor vehicle collisions also increased WBCT usage. Adjusting for casemix, there was a 13-fold intrahospital variation in the use of WBCT between MTCs and a 30-fold variation between TUs/NDHs. The amount of variability between individual hospitals that could not be accounted for by the factors shown to impact on WBCT use was 26% (95% CI 17% to 39%) for MTCs and 17% (95% CI 13% to 21%) for TUs/NDHs. Conclusion: There are significant variations in WBCT use between different hospitals in England and Wales, which require further investigation.